Integrating Digital Media into Islamic Education: Exploring Youtube as a Da’wah Platform for Santri - Bagas Mukti Nasrowi; Mifta Ayu Fadillah (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2026)
This study aims to analyze the utilization of YouTube as a medium for digital da'wah and learning from the perspective of Islamic education at Pondok Pesantren Ayo Ngaji, Pekalongan Regency. This research employs a qualitative approach with an ethnographic design, involving students (santri) who are actively engaged in managing the YouTube channel @KedaiBincang as the research subjects. Data were collected through participatory observation, in-depth interviews, and documentation. The data analysis followed the stages of data condensation, data display, and conclusion drawing. The findings reveal that YouTube is utilized as a digital da'wah medium that aligns with the concept of wasā’il al-da‘wah and is capable of transforming traditional da'wah methods into digital formats. The santri act as content creators who produce and disseminate Islamic values through various forms of content, such as da'wah videos, podcasts, and live streaming. Furthermore, YouTube also functions as a learning medium that promotes a student-centered approach and enhances the santri’s digital literacy, including skills in video editing, communication, and content management. Therefore, the use of YouTube not only expands the reach of da'wah but also strengthens the quality of Islamic education that is adaptive to technological developments in the digital era.